E-218 Risk factors of unexplained early neurological deterioration following endovascular treatment in patient with large vessel occlusion: systematic review and meta-analysis. (23rd July 2022) - Abbasi, M; Arturo Larco, J; Perez Vega, C; Huynh, T
Abstract : Background: Endovascular thrombectomy (EVT) is an effective treatment for acute ischemic stroke attributable largevessel occlusion. However early neurological deterioration (END) remains a serious clinical issue strongly associated with poor outcome. Despite several obvious causes of END that can lead to evidence based management of stroke, a particular END called unexplained EAD (UN-END) exists. Studies on UN-EAD after EVT are limited in the literature. Methods: In February 2022, a comprehensive literature search on risk factors associated UN-END was performed with the keywords including 'Stroke', 'Thrombectomy', 'unexplained early neurological deterioration', and 'Risk Factors'. Their correlations with UN-END were evaluated using a separate random effects model that was fit for each risk factor to calculate pooled mean differences or odds ratios. Results: Three studies with 4336 patients were included in the meta-analysis. The rate of UN-END was 6.4% (95% CI, 4.3%-9.4%). Patients with UN-END had higher Age [mean difference (MD): 3.34, 95% confidence interval (CI): 0.70 to 5.98], Systolic blood pressure [MD: 7.47, 95% CI: 4.54 to 10.41], and lower baseline NIHSS score [MD: -2.48, 95% CI: 4.60 to -0.37] compared to patients with No-UND. Patients with UN-END had more DM [Odds ratio (OD): 1.95, 95% CI: 1.46 to 2.59] and were less likely to have received IV-thrombolysis (OD): 0.75, 95% CI: 0.57 to 0.99]. Other risk factors including gender, Hyperlipidemia, Hypertension, prior stroke, ASPECT score at baseline, and occlusion locations were not statistically significant different between UN-END and no-UND patients. Conclusion: Several risk factors were associated with UN-END for after EVT in particular Age and NIHSS score at baseline. Future research on the mechanism underlying UN-END is warranted. Disclosures: M. Abbasi: None. J. Arturo Larco: None. C. Perez Vega: None. T. Huynh: None.